Community and public health education methods a practical guide - Bensley, Robert J.; Brookins-Fisher, Jodi (Burlington, MA Jones & Barlett Learning, 2019)
"Updated and revised to keep pace with changes in the field, the fourth edition of Community and Public Health Education Methods: A Practical Guide teaches students to effectively communicate health education messages and positively influence the norms and behaviors of both individuals and communities. Written by and for health education specialists, this text explores the methods used by health educators, including didactic techniques designed to guide others toward the pursuit of a healthy lifestyle. The text is divided into three sections, each containing chapters that center on a common theme. Section I focuses on building the foundation for selecting and applying community health education methods, including chapters focusing on theories and models, becoming a professional, promoting multicultural diversity, social marketing concepts, and health communication strategies. Chapters in sections II and III follow a similar format that includes an introduction to the topics, steps for implementing the skill, tips and techniques for successful implementation, strategies for overcoming challenges, and expected outcomes. Features & Benefits: Includes a new chapter focusing on using social media tools, such as Facebook, twitter, Instagram, Pinterest, Snapchat, texting, blogging, smartphone apps, internet channels (e.g., YouTube), video vines, etc; Incorporates the new CHES competencies throughout the book, so that users understand what to expect in terms of CHES within each chapter; Each chapter includes key terms, additional resources, interesting "Did You Know?" facts, and a series of "Community Connections" vignettes designed to provide readers with an easy-to-understand, practical application on the concepts presented"--The publisher.
Foundations for selecting community and public health education strategies -- Becoming a health education professional -- Promoting health education in a multicultural society -- Exploring social marketing concepts -- Building a health communication framework -- Developing effective presentation and training skills -- Developing and selecting resource materials -- Using social media -- Working with media outlets -- Facilitating groups -- Building and sustaining coalitions -- Advocating for health policy -- Using media advocacy to influence policy.
Revised edition of: Community health education methods : a practical guide. 3rd. ed. c2009.
Includes bibliographical references and index.
Keywords: Health education -- Handbooks, manuals, etc; Community health services -- Handbooks, manuals, etc